Hepatic tuberculosis induced by rituximab treatment for C1q nephropathy with minimal change disease: a case report - Wang, Huifang; Huang, Yiqi; Jin, Feng; Liu, Xinxin (Frontiers in Medicine, 2025)
BackgroundRituximab is widely used for autoimmune nephropathy. It depletes B cells, potentially increasing infection risk. Tuberculosis is a rare but severe complication of rituximab treatment. We report a case of liver tuberculosis in a patient with C1q nephropathy with Minimal Change Disease (MCD) treated with rituximab.Case presentationIn March 2023, an 81-year-old male patient was admitted to Shaoxing Second Hospital with a 2-month history of bilateral lower extremity edema. He was diagnosed with C1q nephropathy with MCD through renal biopsy. After treatment with 2 g rituximab, his proteinuria was relieved. In October 2024, due to B-cell rebound, 0.5 g of rituximab was added. In December 2023, the patient visited our hospital due to a 7-day fever. Abdominal ultrasound revealed a non-uniform hypoechoic liver mass suspected to be an abscess. Empirical antibiotic treatment was ineffective and the condition worsened. A liver biopsy was immediately performed, and the pathology showed characteristic granulomatous inflammation and patchy coagulative necrosis. The patient was ultimately diagnosed with hepatic tuberculosis and received a 1-year anti-tuberculosis treatment, including rifampicin 450 mg qd, isoniazid 300 mg qd, pyrazinamide 1,500 mg qd, and ethambutol 1,000 mg qd. The patient’s temperature returned to normal and abdominal pain was relieved on the third day of treatment. Two months later, a follow-up ultrasound showed a reduction in the left lobe liver mass, and an 8-month CT scan showed complete disappearance of the mass. The patient is currently under follow-up.ConclusionRituximab may be an effective treatment option for C1q nephropathy with MCD. Although the risk of infection with rituximab is relatively low, rare infections such as tuberculosis still need to be vigilant, especially in elderly or immunocompromised patients. Additionally, we recommend routine screening for latent tuberculosis in elderly patients with nephropathy and hypogammaglobulinemia before rituximab treatment.